Digital signal processing. - SOMIB, SOMIB (Revista Mexicana de Ingenieria Biomedica, 1991)
The fundamental principles of the theory of signals and systems are based on the idea of making an abstraction of the phenomenon under study. As we will see later, this is achieved through the use of certain mathematical principles and, through the fundamental idea, to represent the problem in question, by a "black box" or system.